Unequal access to higher education in the Czech Republic: The role of spatial distribution of universities - Michal Franta; Martin Guzi (Institute for the Study of Labor (IZA), 2012)
We explore a potential source of human capital spatial disparities: the unequal access to tertiary education caused by the absence/presence of a local university. Because the entrance to a university is a sequential process in the Czech Republic we model both a student's decision to apply to a university and the admission process. Two possible sources of unequal access to university are distinguished: cost savings and informational advantages for those residing close to a university. Estimation results suggest that the presence of a university per se is not driving student's decision to apply. Further we find that information advantage due to university proximity plays a significant role in the admission process. However this advantage is specific to the field of study, and becomes stronger in the case of highly oversubscribed study fields. To equalize the chance of admission, policy makers should consider geographical expansion of the system of universities accompanied by the expansion of university programs.
urn:nbn:de:101:1-201203145346
Keywords: I20; I21; J24; 330; human capital; spatial distribution; access to tertiary education; Bildungschancen; Hochschule; Humankapital; Räumliche Verteilung; Tschechische Republik